Desarrollo vegetativo de naranja bajo estrés hídrico, utilizando diferentes portainjertos naturalizados en la provincia de Loja - Chimbo Muima, Karla Fernanda (2022)
Citrus fruits are a perennial crop of great importance worldwide; that is why the importance of this crop has led to the development of various studies focused on the use of different patterns and the influence that this may have on the vegetative and productive development of the grafted cultivar under different environmental conditions and water stress. The use of rootstocks with promising characteristics has been a highly debated and little known aspect for the vast majority of producers; for this reason, it is necessary to investigate the vegetative development of orange under water stress, using different naturalized rootstocks in the province of Loja. The objective of this work was to evaluate the vegetative development of orange under water stress on different rootstocks of naturalized citrus fruits. The test was carried out in the fifth experimental teacher “La Argelia”. It was established under a design in divided plots with a bifactorial arrangement in the subplot. The treatments were for the main plot the irrigation factor (100 % and 60 % of its CC) and for the subplot, two species of patterns were used (Mandarin Lemon and Sour Orange) and two orange cultivars (Washington Navel and Sanguina) obtaining a total of 48 experimental units with 8 treatments and 6 repetitions. The vegetative variables evaluated were plant height, rootstock diameter, shoot length and diameter, absolute and relative shoot growth rate (TCA and TCR), number of leaves, crown volume, crown diameter and leaf area. The effect of the treatments on the dependent variables was evaluated by ANOVA and DGC test (p <0,05). Although, in most of the variables, no significant effects of the treatments were found for double and triple interactions, an independent effect of the factor rootstock and variety was observed. In this sense, the irrigation factor did not show a significant difference for the vegetative variables; on the other hand, the rootstock favored the variables sprout length, number of leaves, leaf area, diameter and crown volume (p <0,05) obtaining the highest values; while the cultivar factor presented greater influence for the variable plant height. The results of this work indicate that the rootstock species influences the development of orange plants; however, it is necessary to continue the studies in later stages to evaluate the effect on the variables associated with yield and production. Keywords: citrus, rootstock, cultivar, water stress, vegetative development.